2015
DOI: 10.1007/s00266-015-0516-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reduction Mammaplasty Operations on the Spinal Column: Clinical and Radiological Response

Abstract: Patients with macromastia should be considered for reduction mammaplasty before the onset of postmenopausal osteoporosis to improve QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 25 publications
(32 reference statements)
0
31
0
3
Order By: Relevance
“…Although the size of this flexion torque is yet to be reported, 4 vertebral column radiographs of women with large breasts (D+ cup bra size) have revealed significantly greater thoracic kyphosis compared to women with small breasts (A cup bra size) 3 . Thoracic kyphosis has also been found to be significantly reduced post-breast reduction surgery 8,11,12 , although other researchers found no relationship between thoracic kyphosis and breast size in post-menopausal women (mean age 69 years) 5 . Unfortunately, the researchers in this study did not screen for osteoporosis, which might have masked the effects of breast size on thoracic kyphosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although the size of this flexion torque is yet to be reported, 4 vertebral column radiographs of women with large breasts (D+ cup bra size) have revealed significantly greater thoracic kyphosis compared to women with small breasts (A cup bra size) 3 . Thoracic kyphosis has also been found to be significantly reduced post-breast reduction surgery 8,11,12 , although other researchers found no relationship between thoracic kyphosis and breast size in post-menopausal women (mean age 69 years) 5 . Unfortunately, the researchers in this study did not screen for osteoporosis, which might have masked the effects of breast size on thoracic kyphosis.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Berberoglu et al, 17 there was no significant correlation found between postoperative vertebral angle and patient BMI. However, Karabekmez et al 18 established significant correlations between BMI and total excised breast tissue volume ( P = 0.0001) and ΔCL angle postoperatively ( P = 0.03).…”
Section: Resultsmentioning
confidence: 80%
“…A breast reduction surgery can significantly reduce the thoracic kyphosis and lumbar lordosis angles, and are also reported to improve poor posture. [14][15][16] It is well-known that large breasts lead to back and neck pain; however, they can also lead to EFD. In such case, a breast reduction surgery will not relieve the pain.…”
Section: Discussionmentioning
confidence: 99%